KARIES GIGI ANAK SMA BRONKHIALE USIA 3-6 TAHUN (Laporan Penelitian) - Rinati Adrin; Sri Hartini Soemartono; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The aim of this study was to determine the difference of oral hygiene and teeth caries in children with asthma bronchiale, age 3-6 years with several levels of frequency of asthma attack. Fifty children with asthma bronchiale were chosen from Pulmonology Clinic University of Indonesia RSCM. This study used Green and Vermilion to assess the oral hygiene and def-t index for measured caries. The frequency of asthma attack was amount of attack of children using drugs per year. The sample was divided into 3 groups. The first group consists of children with asthma 2-6 attacks per year. Second group with 7-12 attacks per year, and the third group more than 12 times per year. One way ANOVA test showed that the oral hygiene and def-t had significant differences between the three groups (p>0.001). Tukey test showed that oral hygiene had significant differences between the group I-II, I-III, II-III respectively (p>0.001). There was a strong correlation between oral hygiene and frequency of asthma attack (r=0.68), def-t and frequency of asthma attacks (r-0.75), and oral hygiene and caries (r-0.85).